Edaravone Protect against Retinal Damage in Streptozotocin-Induced Diabetic Mice - Yuan, Dongqing (Public Library of Science, 2014)
Edaravone (3-methyl-1-phenyl-2-pyrazolin-5-one), a free radical scavenger, is used for the clinical treatment of retinal injury. In this study, we investigated the protective effects of edaravone against diabetic retinal damage in the mouse. Diabetic retinopathy in the mouse was induced by injection of streptozotocin. Edaravone was given once-daily and was intraperitoneally (i.p.) treated at a dose of 3 mg/kg from streptozotocin injection to 4 weeks after onset of diabetes. Retinal ganglion cells (RGCs) damage was evaluated by recording the pattern electroretinogram (ERG). RGCs damage was also detected by Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) staining, and the levels of reactive oxygen species (ROS) were determined fluorometrically. The expressions of phosporylated-ERK1/2, BDNF, and caspase-3 were determined by Western blot analysis. Retinal levels of ROS, phosphorylated ERK1/2, and cleaved caspase-3 were significantly increased, whereas the expression of BDNF was significantly decreased in the retinas of diabetic mice, compared to nondiabetic mice. Administration of edaravone significantly attenuated diabetes induced RGCs death, upregulation of ROS, ERK1/2 phosphorylation, and cleaved caspase-3 and downregulation of BDNF. These findings suggest that oxidative stress plays a pivotal role in diabetic retinal damage and that systemic administration of edaravone may slow the progression of retinal neuropathy induced by diabetes.